2010
DOI: 10.1002/pro.470
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal domain of the V‐ATPase a2‐subunit displays integral membrane protein properties

Abstract: V-ATPase is a multisubunit membrane complex that functions as nanomotor coupling ATP hydrolysis with proton translocation across biological membranes. Recently, we uncovered details of the mechanism of interaction between the N-terminal tail of the V-ATPase a2-subunit isoform (a2N ) and ARNO, a GTP/GDP exchange factor for Arf-family small GTPases. Here, we describe the development of two methods for preparation of the a2N 1-402 recombinant protein in milligram quantities sufficient for further biochemical, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…20 Similar to our study, Merkulova and co-workers 20 found that the mammalian a2 subunit consists of mostly alpha helical fold and elutes in multiple peaks from a gel-filtration column, consistent with oligomerization of this domain. Strikingly, the protein was stabilized at high pH, indicating similar pH-dependent properties.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…20 Similar to our study, Merkulova and co-workers 20 found that the mammalian a2 subunit consists of mostly alpha helical fold and elutes in multiple peaks from a gel-filtration column, consistent with oligomerization of this domain. Strikingly, the protein was stabilized at high pH, indicating similar pH-dependent properties.…”
Section: Discussionsupporting
confidence: 89%
“…1D), which was consistent with previous observations and secondary structure predictions (ref. 20 and data not shown).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 76%
“…1B). Earlier studies have shown that constructs including more or all the N-terminal residues proved difficult to work with because of the tendency of the proteins to aggregate and susceptibility to degradation (37,38). We therefore decided to generate N-and C-terminal truncations to identify minimal soluble and folded domains that could serve in subunit-subunit interaction studies.…”
Section: Resultsmentioning
confidence: 99%
“…The positions of the A (yellow), B (red), C (brown), E (purple), G (beige), H (orange), and DF (blue) subunits and c-ring (magenta) are also shown (5). The N-terminal cytosolic tail of V-ATPase a-subunit (aN) is situated in parallel to the membrane plane and could have contacts with membrane (66). The position of first 17-amino acid peptide-forming epitope (aN(1-17)) involved in interaction with the Sec-7 domain of cytohesin-2 is also indicated.…”
Section: Arf6mentioning
confidence: 99%